ACT (Aware, Check, Treat): A Community-Based Program to Enhance Adolescents' Awareness and Early Detection of Anemia - Lorensia Panselina Widowati; Sondang Ratnauli Sianturi; Damelya Patricksia Dampang (AMK : Abdi Masyarakat UIKA, 2026)
Adolescent anemia remains a major public health concern in many low- and middle-income countries, including Indonesia and the Philippines. Limited awareness, inadequate nutrition knowledge, and poor preventive practices contribute to the high prevalence of anemia among adolescents, particularly girls. Community-based health education is a promising strategy to improve anemia awareness and encourage early prevention. This community service program aimed to improve adolescents' knowledge and awareness of anemia prevention through the ACT (Aware, Check, Treat) – Teen Anemia Can't Wait educational intervention. The program was implemented in the International Collaboration Trip (ICT) 2025. It was conducted at Manila Central University High School, Philippines, involving 38 students. Most participants were 18 years old (44.4%), enrolled in Grade 12 (66.0%), and female (61.1%). Participants actively engaged in all educational activities and demonstrated a good understanding of the topics discussed. During the evaluation, most students answered questions on the causes, symptoms, prevention, and early detection of anemia correctly and confidently, indicating improved knowledge and awareness following the intervention. The ACT (Aware, Check, Treat) program effectively enhanced adolescents' knowledge and awareness of anemia prevention through interactive and skills-based health education. Similar community-based interventions should be expanded through sustained collaboration among schools, healthcare providers, and families to strengthen adolescent anemia prevention.